Penerapan Teknologi Mesin Penghancur Kotoran Kambing untuk Kelompok Ternak Sekajau Mandiri di Dusun Solor Medan Sambas - Feby Nopriandy; Suhendra Suhendra; Leo Dedy Anjiu (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The partner in this community service activity was the Sekajau Mandiri Goat Farming Group, located in Solor Medan Hamlet, Sumber Harapan Village, Sambas Subdistrict. The main problem faced by the partner was the lack of technology to process goat manure into organic fertilizer. Until now, this livestock group has relied on traditional methods of managing livestock waste. Through this community service activity, efforts were made to solve the problem by applying technology in the form of a livestock manure shredder. The stages of this activity included the manufacture of the machine, testing its capacity, training in operation and maintenance, handover of the livestock manure shredder, and evaluation of the community service results. The livestock waste shredder provided to the partners has a capacity of 167.4 kg/hour. This activity has impacted the partners by increasing the production capacity of their manure fertilizer. The partners can accelerate the production cycle, reduce labor costs, and increase the volume of manure fertilizer available for sale.